Differential Spatiotemporal Expression of Type I and Type II Cadherins Associated With the Segmentation of the Central Nervous System and Formation of Brain Nuclei in the Developing Mouse - Polanco, Julie; Reyes-Vigil, Fredy; Weisberg, Sarah D.; Dhimitruka, Ilirian; Brusés, Juan L. (Frontiers in Molecular Neuroscience, 2021)
Type I and type II classical cadherins comprise a family of cell adhesion molecules that regulate cell sorting and tissue separation by forming specific homo and heterophilic bonds. Factors that affect cadherin-mediated cell-cell adhesion include cadherin binding affinity and expression level. This study examines the expression pattern of type I cadherins (Cdh1, Cdh2, Cdh3 and Cdh4), type II cadherins (Cdh6, Cdh7, Cdh8, Cdh9, Cdh10, Cdh11, Cdh12, Cdh18, Cdh20 and Cdh24), and the atypical Cdh13 during distinct morphogenetic events in the developing mouse central nervous system (from embryonic day (E) 11.5 to postnatal day (P) 56). Cadherin mRNA expression levels obtained by in situ hybridization experiments carried out at the Allen Institute for Brain Science (https://alleninstitute.org/) were retrieved from the Allen Developing Mouse Brain Atlas. Cdh2 is the most abundantly expressed type I cadherin throughout development, while Cdh1, Cdh3 and Cdh4 are expressed at very low levels. Type II cadherins show a dynamic pattern of expression that varies between neuroanatomical structures and developmental ages. Atypical Cdh13 expression pattern is similar to Cdh2 in abundancy and localization. Analyses of cadherin-mediated relative adhesion estimated from their expression levels and binding affinities show substantial differences in adhesive properties between neuromeric segments associated with the regionalization of the neural tube along the anterior-posterior axis. Differences in relative adhesion were also observed between brain nuclei in the developing subpallium (basal ganglia), suggesting that differential cell adhesion contributes to the segregation of neuronal pools. In the adult cerebral cortex, type II cadherins Cdh6, Cdh7, Cdh8, Cdh10 and Cdh12 are most abundant in intermediate layers, while Cdh11 shows a gradated expression from layer 6 to the superficial layer 1, and Cdh9, Cdh18 and Cdh24 are more abundant in the deeper layers. Person's correlation analyses of cadherins mRNA expression patterns between areas and layers of the dorsal pallium and the nuclei of the subpallium show significant correlations between cortical layers and subpallidal nuclei. The study shows that differential cadherin-mediated adhesion is associated wide a range of morphogenetic events in the developing central nervous system leading to the organization of neurons into layers, nuclei and formation of neuronal circuits.